Static and dynamic strength indicators in paralympic power-lifters with and without spinal cord injury - Teles, L. J. L.; Aidar, F. J.; Matos, D. G.; Marcal, A. C.; Almeida-Neto, P. F.; Neves, E. B.; Moreira, O. C.; Ribeiro Neto, F.; Garrido, N. D.; Vilaca-Alves, J. (International Journal of Environmental Research and Public Health, 2021)
Background: In Paralympic powerlifting (PP), athletes with and without spinal cord injury (SCI) compete in the same category. Athletes with SCI may be at a disadvantage in relation to the production of muscle strength and the execution of motor techniques.